Characteristics Associated with Home Health Care Referrals at Hospital Discharge: Results from the 2012 National Inpatient Sample. (16th May 2016) - Jones, Christine D.; Wald, Heidi L.; Boxer, Rebecca S.; Masoudi, Frederick A.; Burke, Robert E.; Capp, Roberta; Coleman, Eric A.; Ginde, Adit A.
Abstract : Objective: To assess patient‐ and hospital‐level factors associated with home health care (HHC) referrals following nonelective U.S. patient hospitalizations in 2012. Data Source: The 2012 National Inpatient Sample (NIS). Study Design: Retrospective, cross‐sectional multivariable logistic regression modeling to assess patient‐ and hospital‐level variables in patient discharges with versus without HHC referrals. Data Collection: Analysis included 1, 109, 905 discharges in patients ≥65 years with Medicare. Principal Findings: About 29.2 percent of discharges were referred to HHC, which were more likely with older age, female sex, urban location, low income, longer length of stay, higher severity of illness scores, diagnoses of heart failure or sepsis, and hospital location in New England (referent: Pacific). Conclusions: As health policy changes influence postacute HHC, defining specific diagnoses and regional patterns associated with HHC is a first step to optimize postacute HHC services.